Comparative and developmental anatomy of the fibularis brevis muscle: morphological variants and their clinical significance - Olewnik, Łukasz; Landfald, Ingrid C.; Domosławska, Daria; Ruzik, Kacper; Triantafyllou, George; Piagkou, Maria; Vázquez, Teresa (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe fibularis brevis muscle (FBM)is a key stabilizer of the lateral ankle, yet its anatomy exhibits a notable degree of variability. While often overshadowed by the fibularis longus, FBM and its tendon (FBT) play critical roles in foot eversion, proprioception, and surgical reconstruction. However, inconsistent terminology and limited integrative studies have hindered comprehensive clinical understanding.MethodsThis review synthesizes data from developmental anatomy, fetal and adult cadaveric dissections, comparative morphology across vertebrates, and clinical imaging. Anatomical classifications of the FBT and fibularis digiti quinti (FDQ) were evaluated alongside their embryological origins, phylogenetic trends, imaging correlates, and surgical relevance.ResultsA unified classification of FBT (Types I–IV) and FDQ (Types 1–3) is proposed, reflecting morphological, developmental, and radiological patterns. The FBM muscle demonstrates modular variability that parallels phylogenetic adaptations from complete absence in certain cursorial mammals to hypertrophy in arboreal primates. Variant tendinous insertions and accessory fascicles may mimic pathology in MRI or complicate surgical dissection.ConclusionFB represents a morpho-evolutionary continuum rather than a static anatomical unit. Recognition of its variants through improved classification, imaging protocols, and evolutionary insight is essential for anatomists, radiologists, and surgeons. This integrative approach advances the clinical and biological understanding of lateral leg musculature.